Doprinos aktivne poti v šolo k celostni gibalni/športni aktivnosti otrok in mladostnikov - Jerina, Tanja; Pišot, Rado (Revija za elementarno izobraževanje, 2014)
The Contribution of Active Journey to School to overall Physical Activity Level of Children and Adolescents. Daily active journey (AJ) to/from school can be an important source of physical activity (PA) of children and adolescents, necessary for their overall development and health preservation. Yet, the relation between AJ to/from school and PA of children and adolescents is still not clear. The purpose of this article is to find out whether the AJ to/from school influences the rise of PA. Systematic examination of electronic databases such as MEDLINE, Google Scholar, Science Direct and Springerlink, in May 2012 helped us find relevant articles of which 18 met the criteria for inclusion in our review. Studies include children and adolescents aged 5 to 16 years and quantitatively analyse the relationship between AJ and PA. Fourteen out of eighteen studies report that children and adolescents who practice AJ accumulate more PA compared to those who are driven to/from school. At the same time 8 studies report a positive correlation between AJ to/ from school and moderate to vigorous physical activity (MVPA). More longitudinal studies would be necessary to get a deeper insight into the link between AJ and PA. Establishing uniformed criteria for monitoring AJ and PA and monitoring factors that influence the decision for the AJ would contribute to comparability of the results of individual studies and would at the same time make the development of effective intervention programmes for encouraging AJ among children and adolescents possible.
Keywords: active journey; physical activity; accelerometer; children; adolescents